100 Impact of smoking on total and major causes of mortality among Chinese silicotics in Hong Kong: effect modifier or confounder?. (11th October 2013) - Yu, I; Tse,; Qiu,; Leung,
Abstract : Objectives: Whether smoking being an effect modifier or confounder in increased total mortality and mortality from major causes has never been formally evaluated in occupational cohort studies and this lack of knowledge was addressed in a cohort of Chinese workers with silicosis. Methods: All workers with silicosis in Hong Kong diagnosed during the period 1981–2005 were followed up till the end of 2006 to ascertain their vital status and causes of death. An index of 'relative silicosis effect (RSE)' was used to examine the potential multiplicative interaction between smoking and silicosis. A smoking indirectly adjusted standardised morality ratio (SMR) according to the method of 'smoking adjustment factor (SAF)' was presented if the RSE was not statistically significant (i.e., no multiplicative interaction). Results: The RSE for total deaths and the deaths from non-malignant respiratory diseases (NMRD) was 0.75 (95% CI: 0.62–0.91) and 0.59 (95%CI: 0.46–0.78); however, it was not statistically significant for other specific causes of death. Smoking indirectly adjusted SMR for oesophagus cancer, lung cancer, chronic obstructive pulmonary diseases, silicosis, pulmonary tuberculosis and pulmonary heart disease was 1.08 (95% CI: 0.72–1.64), 1.24 (95% CI: 1.06–1.45), 2.07 (95% CI: 1.78–2.41), 411.35 (95% CI: 377.03–448.79), 4.99 (95% CI: 3.80–6.54), and 4.09 (95% CI: 2.55–6.54). Conclusions: This historical cohort study demonstrated a significant multiplicative interaction between smoking and silicosis on the mortality of total deaths and deaths from NMRD; however, smoking was more likely to play a role of confounding in an increased mortality from other major causes among Chinese silicotic workers.